A Pectin Methylesterase ZmPme3 Is Expressed in Gametophyte factor1-s (Ga1-s) Silks and Maps to that Locus in Maize (Zea mays L.) - Moran Lauter, Adrienne N.; Muszynski, Michael G.; Huffman, Ryan D.; Scott, M. Paul (Frontiers in Plant Science, 2017)
The ga1 locus of maize confers unilateral cross incompatibility, preventing cross pollination between females carrying the incompatible Ga1-s allele and males not carrying a corresponding compatible allele. To characterize this system at the molecular level, we carried out a transcript profiling experiment in which silks from near isogenic lines carrying the Ga1-s and ga1 alleles were compared. While several differentially expressed genes were identified, only one mapped to the known location of ga1. This gene is a pectin methylesterase (PME), which we designated as ZmPme3, and is present and expressed only in Ga1-s genotypes. While a functional ZmPME3 is not present in the ga1 genotypes examined, a pectin methylesterase gene cluster is found in ga1 genotypes. The gene cluster in W22 contains 58 tandem full-length or partial PME pseudo genes. These data combined with a wealth of previously published data on the involvement of PMEs in pollen tube growth suggest a role for cell wall modification enzymes in the pollen exclusion component of Ga1-s gametophytic incompatibility. Consistent with this role, a third allele which lacks the female function of Ga1-s, Ga1-m, has a mutationally inactivated version of ZmPme3.